Ideal stoichiometric technetium nitrides under pressure: a first-principles study - Zhao, Z.L.; Bao, K.; Duan, D.F.; Jin, X.L.; Tian, F.B.; Li, D.; Liu, B.B.; Cui, T. (Сверхтвердые материалы, 2014)
Technetium nitrides with various ideal stoichiometries have been investigated with the first-principle method at the pressures between 0–60 GPa. It have been found that there could be many stable technetium nitrides including Tc₃N, Tc₂N, TcN, Tc₂N₃, TcN₂, TcN₃, and TcN₄, among which Tc₃N and Tc₂N sub-nitrides are synthesizable at zero pressure and could be applied to nuclear waste management, such as separate radioactive 99Tc from nuclear fuel cycle. Moreover, N-rich TcN₃ and TcN₄ exhibit remarkable bulk properties and can be potential ultrastiff and hard materials. Нітриди технеція з різною ідеальної стехіометрією досліджені із застосуванням методу перших принципів при тисках від 0 до 60 ГПа. Встановлено, що може бути багато стабільних нітридів технеція, включаючи Tc₃N, Tc₂N, ТКС, Tc₂N₃, TcN₂, TcN₃ і TcN₄, серед яких субнітриди Tc₃N і Tc₂N синтезуються при нульовому тиску і можуть бути використані для обробки ядерних відходів, таких як виділений при ядерному паливному циклі радіоактивний 99Tc. Більш того, TcN₃ і TcN₄, збагачені N, демонструють чудові об’ємні властивості і можуть бути потенційними ультражорсткими і твердими матеріалами. Нитриды технеция с различной идеальной стехиометрией исследованы с применением метода первых принципов при давлениях от 0 до 60 ГПа. Установлено, что может быть много стабильных нитридов технеция, включая Tc₃N, Tc₂N, ТКС, Tc₂N₃, TcN₂, TcN₃ и TcN₄, среди которых субнитриды Tc₃N и Tc₂N синтезируются при нулевом давлении и могут быть использованы для обработки ядерных отходов, таких как выделенный при ядерном топливном цикле радиоактивный 99Tc. Более того, TcN₃ и TcN₄, обогащенные N, демонстрируют замечательные объемные свойства и могут быть потенциальными ультражесткими и твердыми материалами.